Software to productive and reproductive control of goats: PROCAPRI - Ribeiro, SDA; Resende, Kleber Tomás de [UNESP]; Goncalves, AAM; Ribeiro, A. C.; Bertoldi, J. L.; Sanches, A. C.; Naka, R. J. (Amer Soc Agr Engineers, 1998)
PROCAPRI is a software to productive and reproductive control of goats developed with the aim of assisting the goat producers in their decisions, to make a representative data set of Brazilian goats production and providing research information. It has five modules: Administration, Association, UNESP, Maintenance, and Utilities. It has been available since October 1994, and it has been amply used, with 157 copies distributed until April 1998 in Brazil and other countries.
Keywords: goat; management; productive control; reproductive control; Software